Implementing the Use of Canva Media to Promote Interest in Reading and Writing the Qur'an in Primary Schools - Cindy Tri Vidiawati; Istikomah Istikomah (UMSU, 2023)
The purpose of this study is to describe how teachers use Canva media in promoting interest in Qur'anic reading and writing. The research involved a type of research using a case study model with the research scene of SDN Sumorame as one of the public primary schools implementing BTQ using Canva media. After the data was collected, the researcher analysed it using a qualitative analysis approach narrative model. The data collection techniques were observation, interview and documentation. The results of the study explain that Canva media is able to promote interest in reading among students, proven by: (1) the existence of features in Canva that are attractive such as graphic design, (2) posters that promote attractiveness for elementary school students, (3) the existence of videos and animations related to the laws of Tajweed reading, (4) Canva media is flexible because it can be played on android phones and computers with the help of an internet connection.